2017
DOI: 10.1002/uog.17216
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian masses with papillary projections diagnosed and removed during pregnancy: ultrasound features and histological diagnosis

Abstract: In pregnant women, ovarian cysts with ground-glass echogenicity and papillations with a smooth contour on ultrasound are most likely to be decidualized endometriomas. Cysts with anechoic or low-level echogenicity and papillations with an irregular contour suggest borderline malignancy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
(38 reference statements)
1
20
1
Order By: Relevance
“…Tajima et al 28 used six patterns of echogenicity to distinguish between benign masses and BOT/malignant ovarian tumors, but likewise did not highlight any defining features unique to BOTs and grouped them with malignant entities. Mascilini et al 29 and Moro et al 30 employed the IOTA criteria with the previously described five benign and five malignant features 18 and determined that BOTs were likely to have between two and 10 loculations on imaging. Pascual et al 23 studied BOTs and, using multivariate analysis, determined that the only predictive sonographic feature was the presence of papillae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tajima et al 28 used six patterns of echogenicity to distinguish between benign masses and BOT/malignant ovarian tumors, but likewise did not highlight any defining features unique to BOTs and grouped them with malignant entities. Mascilini et al 29 and Moro et al 30 employed the IOTA criteria with the previously described five benign and five malignant features 18 and determined that BOTs were likely to have between two and 10 loculations on imaging. Pascual et al 23 studied BOTs and, using multivariate analysis, determined that the only predictive sonographic feature was the presence of papillae.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the novelty and importance of our findings, we carried out a PubMed search of the English-language literature published between 2010 and 2018, seeking to determine if this microcystic tissue pattern of papillary projections, solid component(s) and/or septa has been described previously. Figure S3 is a composite of images found on review of 23 articles 6,[16][17][18][22][23][24][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] identifying 163 individual sonographic pictures of ovarian cysts labeled as BOT by the authors. Although the quality of these images is variable, on close examination it is clear that almost all of them feature a 'bubbly' microcystic nature of papillae or solid component(s).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recent articles have described the use of the IOTA models to diagnose ovarian cancer during pregnancy. 9,12 The results of the available studies are extremely encouraging, although limited by the inevitably low number of patients enrolled. In the present case report, the description of the mass in accordance with the terminology proposed by the IOTA group allowed us to correctly diagnose the presence of a borderline ovarian mass in this pregnant adolescent patient.…”
Section: Discussionmentioning
confidence: 99%
“…From the beginning of this century, the role of ultrasound in the first trimester of pregnancy has been useful to study adnexal masses occasionally found during fetal examination. 9 Studies about the risk of malignancy of pelvic masses are few and retrospective, with inevitably limited results. [10][11][12] The International Ovarian Tumor Analysis (IOTA) protocol has been recently suggested as a very useful tool to identify description patterns to standardize the ultrasonographic examinations.…”
mentioning
confidence: 99%
See 1 more Smart Citation